Clinical Outcomes of the Oral Suspension vs Delayed-Release Tablet Formulations of Posaconazole for Prophylaxis of Invasive Fungal Infections. (4th October 2017) - Tallman, Gregory B; Furuno, Jon P; Noble, Brie N; Bubalo, Joseph S; Forrest, Graeme N; Lewis, James S; Bienvenida, Ana F; Holmes, Courtney A; Weber, Bo R; McGregor, Jessina C
Abstract: Background: Posaconazole is effective prophylaxis for invasive fungal infections (IFIs). We compared incidence of breakthrough IFI (bIFI) and early posaconazole discontinuation between patients receiving delayed-release tablet and oral suspension formulations. Methods: This was a retrospective cohort study of patients receiving posaconazole at Oregon Health & Science University Hospital between 1/1/2010 and 6/30/2016. Oral suspension was the preferred formulation until 2/2014; afterwards the tablet was preferred. We included all courses of primary prophylaxis for each patient during the study period. Data were extracted from an electronic health record repository and via chart review. Three independent reviewers identified bIFI using European Organization for Research and Treatment of Cancer criteria. We assessed rationale for early discontinuation of posaconazole for patients that were still indicated for antifungal prophylaxis based on National Comprehensive Cancer Network (NCCN) criteria. Results: 547 patients received 859 courses of posaconazole (53% oral suspension and 48% tablet). Prophylaxis was indicated according to NCCN criteria in 91% of courses. The primary indications for prophylaxis were acute myelogenous leukemia (68%), graft-vs-host disease (18%), and myelodysplastic syndrome (3%). There were no significant differences in demographics or indication between patients receiving the different formulations. The overall incidence rate of bIFI was 4.15/10, 000 posaconazole-days (16 total bIFI events). Incidence of bIFI was not significantly different between patients receiving the different formulations ( P = 0.92). Posaconazole was discontinued early in 147 (17%) courses; frequency of discontinuation was not significantly different between the tablet (20%) and oral suspension (15%) formulations ( P = 0.10). The primary reasons for early discontinuation were elevated liver function tests or QT prolongation (25%), inability to take an oral formulation (17%), and drug cost (17%). Conclusion: Among patients receiving posaconazole prophylaxis, incidence of bIFI was low and not significantly different between those receiving the tablet vs oral suspension formulations. Disclosures: J. P. Furuno, Merck & Co.: Consultant and Grant Investigator, Consulting fee, Research grant and Speaker honorarium. J. S. Lewis II, Merck & Co.: Consultant, Consulting fee. J. C. McGregor, Merck & Co.: Grant Investigator, Research grant